Investigations on Three Phase Five Switch Multilevel Inverter with Reduced Number of Switches - Balamurugan, C.R; Natarajan, S.P; Arumugam, M; Bensraj, R (Review of Industrial Engineering Letters, 2014)
The multi-level inverter system is mostly used in ac drives, when both reduced harmonic contents and high power are required. In this paper a new topology of multilevel inverter is introduced. This type has many steps with less power electronic switches. Due to the less number of switches the cost of the inverter is very less and also less installation area is required. Firstly, we describe briefly the structural parts of the inverter then switching strategy and operational principles of the proposed inverter are explained and operational topologies are given. Simulation is performed using MATLAB SIMULINK. Various conventional PWM techniques are applied to the circuit such as PDPWM, PODPWM, APODPWM, VFPWM and COPWM. By comparing among the conventional PWM techniques, PDPWM provide the less THD value and COPWM provide a higher fundamental RMS output voltage.